2021
DOI: 10.1063/5.0058884
|View full text |Cite
|
Sign up to set email alerts
|

One-stage simplified lattice Boltzmann method for two- and three-dimensional magnetohydrodynamic flows

Abstract: In this paper, we propose a new simplified lattice Boltzmann method (SLBM) for magnetohydrodynamic flows that outperforms the classical one in terms of accuracy, while preserving its advantages. A very recent paper [A. De Rosis, J. Al-Adham, H. Al-Ali and R. Meng, "Double-D2Q9 lattice Boltzmann models with extended equilibrium for two-dimensional magnetohydrodynamic flows", Phys. Fluids 33, 035143 (2021)] demonstrated that the SLBM enforces the divergence-free condition of the magnetic fiield in an excellent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Furthermore, it will be interesting to examine Hall-MHD flows by generalizing the studies in the following lattice Boltzmann models (LBM) papers on MHD flows that have appeared recently. 76…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it will be interesting to examine Hall-MHD flows by generalizing the studies in the following lattice Boltzmann models (LBM) papers on MHD flows that have appeared recently. 76…”
Section: Discussionmentioning
confidence: 99%
“…Compressible MHD turbulence was studied by Yang et al 26 The authors investigated which turbulence theories proposed for the incompressible cases would be also valid for compressible cases. An alternative approach to simulate magnetohydrodynamic flows, namely, the one-stage simplified lattice Boltzmann method, was proposed by De Rosis et al 27 The accuracy and computational efficiency of this method were demonstrated, making it a good alternative approach for predicting MHD flows.…”
Section: Introductionmentioning
confidence: 99%